Complaints and complaining Functions, antecedents, and consequences. [article]. - Kowalski, Robin M.
Although everyone complains at least occasionally, surprisingly little research attention has been devoted to the topic of complaining. In this review, complaints are defined as expressions of dissatisfaction, whether subjectively experienced or not, for the purpose of venting emotions or achieving intrapsychic goals, interpersonal goals, or both. A theoretical model of complaining is presented that examines the relationship between self-focus, the perceived utility of complaining, and complaining. In addition, the article examines variables related to people's dissatisfaction and complaining thresholds (i.e., negative affect, locus of control, self-presentational concerns, age, and gender), functions of complaining, and intrapersonal and interpersonal consequences of complaining. -- (from the author)